2017
DOI: 10.1158/2159-8290.cd-16-1417
|View full text |Cite
|
Sign up to set email alerts
|

The CREBBP Acetyltransferase Is a Haploinsufficient Tumor Suppressor in B-cell Lymphoma

Abstract: Inactivating mutations of the CREBBP acetyltransferase are highly frequent in diffuse large B-cell lymphoma (DLBCL) and follicular lymphoma (FL), the two most common germinal-center (GC) derived cancers. However, the role of CREBBP inactivation in lymphomagenesis remains unclear. Here we show that CREBBP regulates enhancer/super-enhancer networks with central roles in GC/post-GC cell fate decisions, including genes involved in signal transduction by the B-cell receptor and CD40 receptor, transcriptional contro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
226
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 194 publications
(248 citation statements)
references
References 50 publications
16
226
1
1
Order By: Relevance
“…While this paper was under review, 2 papers interrogating the role of Crebbp inactivation in murine B-cell lymphoma models were published. 34,49 Jiang et al reported downregulation of MHC class II genes with short hairpin RNA-mediated knock-down of Crebbp, but this was not reported by Zhang et al, using B-cell-specific deletion of Crebbp with cre recombinase, and only modest changes were shown in our study. The role of Crebbp loss compared with Crebbp KATdomain point mutation in the deregulation of MHC class II expression therefore requires further functional interrogation.…”
Section: Discussioncontrasting
confidence: 90%
“…While this paper was under review, 2 papers interrogating the role of Crebbp inactivation in murine B-cell lymphoma models were published. 34,49 Jiang et al reported downregulation of MHC class II genes with short hairpin RNA-mediated knock-down of Crebbp, but this was not reported by Zhang et al, using B-cell-specific deletion of Crebbp with cre recombinase, and only modest changes were shown in our study. The role of Crebbp loss compared with Crebbp KATdomain point mutation in the deregulation of MHC class II expression therefore requires further functional interrogation.…”
Section: Discussioncontrasting
confidence: 90%
“…The role of BCL6 in ABC lymphomas remains largely unknown and it is possible that its alteration is required only for initiation of this lymphoma subtype (18), although recent reports indicate that activated B-cell lymphomas may require sustained BCL6 activity (19). As above, KMT2D and CREBBP are frequently mutated in follicular lymphoma and DLBCL and have also been implicated in B-cell maturation specifically via a reduction in CD40L and cytokine responsive transcription (8,9,20). The loss of chromatin modifiers in multiple lymphoma subtypes indicates that chromatin regulation may be critical at multiple points along the B-cell lineage.…”
Section: Introductionmentioning
confidence: 99%
“…Transitioning to the GC phenotype involves deep remodeling of the 3D architecture of the genome and extensive redistribution of epigenetic marks. Activation of BCL6 target genes in the light zone is mediated by the histone acetyltransferases CREBBP and EP300, and the histone methyltransferase KMT2D 88,95,103,104. 87,101 These genes are not "silenced," but instead are simply held in a poised configuration, where RNA Pol II is present and loaded at promoters but is not actively transcribing nascent mRNAs.…”
mentioning
confidence: 99%